Regional Patterns in Bog Body Distribution – A Case Study from the UK. Issue 1 (3rd July 2019) - Stevens, Jessica; Chapman, Henry
ABSTRACT: Recent programmes of dating, forensic examination and landscape studies have dramatically increased our understanding of well-preserved bog bodies. However, other examples, often existing only as 'paper bodies', remain less visible within debates about interpretation, but can provide a more comprehensive picture of what bog bodies represent. This paper presents the results of an examination of all known bog bodies found across England, Wales and Scotland, arguing that a geographical approach provides very different outcomes compared with focusing on the well-preserved bodies in collections. Specifically, we highlight that firstly, previous assumptions about the predominant dates of bog bodies are incorrect, secondly that there are significant sub-regional patterns in the data, and thirdly, that the correlation between body date and the date of discovery provides a likely reason for this bias. Despite this, the evidence reinforces the exceptional pattern of violent deaths being a significant feature of Iron Age/Romano-British period bog bodies.